Ecolinguistics: Critical Perspectives of Eco-friendly Stakes in Selected Anglophone African Literature - Loko, Djima Crépin; Guézohouèzon, Moustafa; Koutchadé, Innocent Sourou (Journal of Ecohumanism, 2025)
As underpinning mobiles of climate change, ecosystemic degradation and environmental pollution are two major global threats to-date. Thus, protecting the nature has turned a shared concern to all researchers, including scientists, philosophers, sociologists, artists, activists, and linguists. The current study aims then to highlight the contribution of English Applied Linguistics to the common battle. Leaning on an eclectic research methodology coupling tools inherent in both Systemic Linguistics and Pragmatics, this work is a trans-textual Critical Discourse Analysis of systematically culled statements from a few Anglophone African writings testifying that literature is a handy channel of brainwashing for eco-friendly sensitization worth taking considerately.